Evaluation of marginal and internal gaps of metal ceramic crowns obtained from conventional impressions and casting techniques with those obtained from digital techniques - Rathika Rai; S Arun Kumar; R Prabhu; Ranjani Thillai Govindan; Faiz Mohamed Tanveer (Wolters Kluwer Medknow Publications, 2017)
Background: Accuracy in fit of cast metal restoration has always remained as one of the primary factors in determining the success of the restoration. A well-fitting restoration needs to be accurate both along its margin and with regard to its internal surface. Aim: The aim of the study is to evaluate the marginal fit of metal ceramic crowns obtained by conventional inlay casting wax pattern using conventional impression with the metal ceramic crowns obtained by computer-aided design and computer-aided manufacturing (CAD/CAM) technique using direct and indirect optical scanning. Materials and Methods: This in vitro study on preformed custom-made stainless steel models with former assembly that resembles prepared tooth surfaces of standardized dimensions comprised three groups: the first group included ten samples of metal ceramic crowns fabricated with conventional technique, the second group included CAD/CAM-milled direct metal laser sintering (DMLS) crowns using indirect scanning, and the third group included DMLS crowns fabricated by direct scanning of the stainless steel model. The vertical marginal gap and the internal gap were evaluated with the stereomicroscope (Zoomstar 4); post hoc Turkey's test was used for statistical analysis. One-way analysis of variance method was used to compare the mean values. Results and Conclusion: Metal ceramic crowns obtained from direct optical scanning showed the least marginal and internal gap when compared to the castings obtained from inlay casting wax and indirect optical scanning. Indirect and direct optical scanning had yielded results within clinically acceptable range.